A discovery of nanoscale sulfide droplets in MORB glasses: implications for the immiscibility of sulfide and silicate melts - Zuo, Lei; Zhang, Peng; Wang, Ya-qin; Liu, Rui (Frontiers in Earth Science, 2024)
Sulfur forms an immiscible liquid upon saturation in magma, and sulfide droplets are commonly found in fresh mid-ocean ridge basalt (MORB). Scanning electron microscopy (SEM) analysis revealed that the fine-grained and weakly phyric MORB samples exhibited hypocrystalline to vitreous textures. Transmission electron microscopy (TEM) of MORB glasses exhibit nanoscale sulfide droplets (10-15 nm) with rounded shapes and smooth edges, showing crystalline and homogeneous composition. Elemental distribution included S, Fe, Cu, and Ni, while Si, Al and O are lacking. Prior research clarified the immiscibility between sulfide and silicate melts, impacting the size distribution of sulfide droplet. This is the first report on nanoscale sulfide droplets within MORB glasses, and these results suggest that nanoscale sulfide droplets represent the initial phase of sulfide saturation; such insight may prove useful in understanding how siderophile and chalcophile elements behaved during sulfide crystallization. In addition, this study determines the immiscibility of sulfides and silicate melts occurred in the early nanometer stage. Therefore, it is speculated that immiscibility phenomena may occur in the nanometer stage during magma evolution.